History and Japanese South Korea Trade Wars - Fahrizal Nugroho; M Mossadeq Bahri (Japanese Research on Linguistics, Literature, and Culture, 2019)
The trade war between Japan and South Korea is now entering a new phase. South Korea is currently counteracting by boycotting goods originating from Japan, such as FMCG (fast-moving consumer goods) companies, fast retaling and automotive. Japan itself has now downgraded the status of South Korea which was originally included in group A or White List Countries or Preferred Trade Partner List Countries into group B, namely countries and regions participating in international export control regimes and satisfying certain conditions (Excluding those in group A) . As we know, this trade war was preceded by restrictions on exports by Japan to South Korea. In July, Japan imposed tighter controls on the export of three raw materials in chips and smart phone screens to South Korea. The materials are photoresists used in the semiconductor industry, hydrogen fluoride as a material for making chips and fluorinated polymides that are used as materials for making smartphone screens. These goods are very important for the industry in South Korea, especially in the smartphone industry, thus making South Korea furious about the Japanese action. The issue that will be raised is how history can shape decision-making in relations between Japan and South Korea, leading to a trade war like today. Relations between Japan and South Korea are very close to what happened in the past. Even today, South Korea still voiced its past suffering caused by Japan and raised tension between the two countries. South Korea plans to file complaints over tightening Japanese export controls to the World Trade Organization (WTO). South Korea accuses Tokyo of having "political motivation" and "discrimination" in the two countries' growing conflict and rooted in wartime history.